Bendamustine and Rituximab in Relapsed and Refractory Hairy Cell Leukemia - Burotto, Mauricio (2013)
PURPOSE: To determine tolerability and for the first time explore efficacy of bendamustine plus rituximab (BR) in multiply relapsed/refractory hairy cell leukemia (HCL), using 2 different dose levels of bendamustine. EXPERIMENTAL DESIGN: HCL patients with ≥2 prior therapies requiring treatment received rituximab 375 mg/m(2) days 1 and 15, plus bendamustine 70 (n=6) or 90 (n=6) mg/m(2), days 1 and 2, for 6 cycles at 4-week intervals. RESULTS: At 70 and 90 mg/m(2)/dose of bendamustine, overall response rate was 100%, with 3 (50%) and 4 (67%) complete remissions (CR) in each respective group. Minimal residual disease (MRD) was absent in 67% and 100% of CRs, respectively. All 6 without MRD remain in CR at 30–35 (median 31) months of follow-up. Soluble CD22 and CD25 levels decreased with all responses, with median values decreasing from 17.7 and 42 ng/ml at baseline to undetectable and 2 ng/ml after CR, respectively (p<0.001). Of 12 patients receiving 72 cycles of BR, the most common toxicities were hematologic, including thrombocytopenia (83%), lymphopenia (75%), leukopenia (58%) and neutropenia (42%). Grade 3–4 hematologic toxicity included lymphopenia and thrombocytopenia (each 75%), leukopenia (58%), and neutropenia (25%). No significant dose-related differences were detected in response or toxicity. CONCLUSION: BR has significant activity in HCL. Bendamustine at either 70 or 90 mg/m(2)/dose was highly effective in multiply relapsed/refractory HCL, and could be considered for achieving durable CRs without MRD in patients after failure of standard therapies. Since it was not dose-limiting, 90 mg/m(2)/dose was chosen for future testing.